The influence of employee engagement, motivation, and work stress on the performance of Perhutani employees in Gresik - Rismayadi, Baiq Irma; Rizqi, Maulidyah Amalina (Review of Management, Accounting, and Business Studies, 2022)
The decline in work results and the non-achievement of company targets can be one of the benchmarks related to employee performance. This contributes to achieving goals and profits for the company. The failure to achieve goals or contribute to increasing production quantity indicated a decline in employee performance at Perhutani Gresik. The objectives of this study were: (1) Understanding the impact of employee engagement on performance at Perhutani Gresik. (2) Examining the influence of work motivation on performance at Perhutani Gresik. (3) Investigating the correlation between work stress and employee performance at Perhutani Gresik. The sample was taken using a saturated sampling technique with a subject of 77 employees of Perhutani Gresik. Based on the results of multiple linear regression analysis, it was found that the employee engagement variable (X1) on employee performance (Y) obtained a significant value of 0.000 smaller than 0.05, which meant that employee engagement had a significant effect on employee performance. The work motivation variable (X2) obtained a significant value of 0.000 smaller than 0.05, which meant that work motivation had a significant effect on employee performance. The variable work stress (X3) on employee performance obtained a significant value of 0.152, which is greater than 0.05. This indicates that work stress partially does not have a significant effect on employee performance. In conclusion, the study at Perhutani Gresik sheds light on crucial factors influencing employee performance. The decline in work results and failure to meet company targets serve as key indicators of diminished performance. The research objectives aimed at understanding the impact of employee engagement, work motivation, and work stress on performance were successfully addressed.